2010
DOI: 10.1109/toh.2010.3
|View full text |Cite
|
Sign up to set email alerts
|

Field-Based Validation of a Tactile Navigation Device

Abstract: In this paper, we present three field-based evaluations of a tactile land navigation system. In Experiment 1, we transition from a laboratory setting to rugged terrain used to train US Army soldier land navigation. Navigation in this challenging terrain requires careful attention to one's surroundings. Participants navigated 3 waypoints along 600 meters through heavily wooded terrain, using 1) map and compass, 2) standard alpha-numeric handheld GPS device, and 3) the tactile GPS system, while also responding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 31 publications
3
71
2
Order By: Relevance
“…Previous work indicates that tactile displays used to convey navigation information can improve the users' attention. It was found that people are able to spot more entities they are tasked to search for [3] and pay more attention to their immediate surroundings, such as obstacles and other people [14]. However, in the study presented here the participants neither felt less distracted nor spotted more benches.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Previous work indicates that tactile displays used to convey navigation information can improve the users' attention. It was found that people are able to spot more entities they are tasked to search for [3] and pay more attention to their immediate surroundings, such as obstacles and other people [14]. However, in the study presented here the participants neither felt less distracted nor spotted more benches.…”
Section: Discussioncontrasting
confidence: 56%
“…It has been shown that vibro-tactile stimuli around the torso can easily be interpreted as pointing directions [27]. This kind of information presentation technique has successfully been used to "drag" people towards waypoints [28] while reducing the distraction at the same time [3,14]. With respect to map-based navigation it has been shown that cueing the general direction of the destination can improve the navigation performance and reduce the distraction [15,22].…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…An often reached conclusion is that congruent visual and vibrotactile feedback improves the quality of gestures, whereby vibrotactile feedback alone allows for faster responses than visual feedback, probably because of the lower induced cognitive load (Rodríguez et al, 2010). Vibrotactile cues for guidance have also been explored for pedestrian (Elliott et al, 2010) and vehicle (Van Erp et al, 2004;Ege et al, 2011) navigation, concluding that tactile feedback functions best in situations with high visual cognitive load and concurrent tasks.…”
Section: Introductionmentioning
confidence: 99%